A new and four known species of Diphtherophora (Nematoda: Diphtherophoridae) from Iran, with a diagnostic compendium of its species - Ghaderi, Reza; Kashi, Leila; Karani, Hossein Mirbabaei; Karegar, Akbar (Zootaxa, 2017)
A new and four known species of the genus Diphtherophora—D. geraerti sp. n., D. caudata, D. obesa, D. perplexans and D. tenera—were collected and identified from different plants and localities in Iran. Morphological and morphometric characters of Diphtherophora geraerti sp. n. are compared with those of closely-related species, including D. siddiqii, D. brevicollis, D. lata, D. obesa, D. citri, D. vasilevi and D. vitoshae. Females of the new species have a head continuous with the body contour, spear 11–14 µm in length, rod-shaped spermatozoa and conical tail with bluntly rounded to hemispherical terminus. Males have two ventromedian neck papillae located 22–25 and 52–60 µm from the anterior end, and two ventromedian supplements at 11–13 and 75–80 µm anterior from cloacal aperture, respectively. All Diphtherophora species recovered as part of the present study are new records for the Iranian nematode fauna. Finally, a diagnostic compendium is given, to assist with species identification in the genus.